Responsividade e interpretabilidade do World Health Disability Assessment Schedule (WHODAS) 2.0 após um programa de exercícios físicos em pacientes com insuficiência cardíaca - Martins, Cristiany Azevedo (2024)
INTRODUCTION: Heart Failure (HF) is a complex clinical syndrome that results in physical disability and loss of functional independence, making life difficult for patients with HF and potentially degrading their quality of life. Despite the ease of estimating functional capacity using validated instruments, very little is known about the prevalence and severity of deficits in activities of daily living in this population. Therefore, the World Health Organization Disability Assessment Schedule (WHODAS) 2.0 can be an important instrument to verify positive or negative impacts on rehabilitation services for patients with HF as it is an instrument that generally measures functionality and disability in the main domains. of life. OBJECTIVE: To verify the responsiveness and interpretability of WHODAS 2.0 in patients with HF undergoing cardiovascular rehabilitation (CVR). METHODOLOGY: This is a responsiveness study with a sample of 40 individuals diagnosed with HF who underwent a supervised cardiovascular rehabilitation program for 8 weeks and were subjected to the following assessment instruments: WHODAS 2.0, 36-item version, Classification functional capacity by the New York Heart Association (NYHA), 6-minute walk test (6MWT), Quality of Life Questionnaire, Functional Capacity estimated by the Duke Activity Status Index (DASI), and Hand Grip Strength (HGS) before and at the end from the program. Statistical analyzes were performed using the R and JAMOVI version 2.3 programs. Responsiveness to rehabilitation therapy was assessed using the Wilcoxon test. RESULTS: The majority were female (n=22, 55%), with HF of the preserved ejection fraction type (n=21, 52.5%), mean age of 62.1±13.4 years, Fraction left ventricular ejection average of 50.8±15.5%. There was an improvement in the 6MWT (p=0.003), dominant HGS (p=0.015), quality of life (p<0.001) and an improvement in all domains of the WHODAS 2.0, however without statistical difference in cognition, self-care, interpersonal relationships and work activities (p>0.05). In the correlations between the variables, only a weak correlation was observed between domestic activities and DASI and HGS. CONCLUSION: WHODAS 2.0 is a responsive instrument, as it was able to detect changes in patients' health status. However, it was not possible to predict a delta of improvement in the WHODAS 2.0 score capable of estimating a minimum clinically important difference for the studied population.